Analisis Penerimaan dan Kesuksesan Menggunakan TAM dan Delone & McLean - Lestari, Indah; Amin, Faris Muslihul; Wahyudi, Noor (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2025)
E-Commerce is a platform that provides various needs, ranging from personal needs, household needs to general needs online. E-Commerce is getting public attention because it can be an alternative convenience in meeting the consumptive needs of the community. Although e-commerce has offered convenience for users, e-commerce also has various weaknesses such as order errors, lack of seller response, fear of fraud, and so on. This is the reason for this research which aims to determine the factors that can affect the acceptance of e-commerce in society and the factors that influence the success of e-commerce. This study uses 400 respondent data which will be processed using Smart-PLS software. Based on data processing, the variables perceived usefulness and perceived ease of use have a positive and significant effect on behavioral intention, information quality and system quality variables have a positive and significant effect on user satisfaction, user satisfaction and behavioral intention variables have a positive and significant effect on net benefits, variable behavioral intention has a positive and significant effect on actual system use. Meanwhile, the service quality variable has a positive and insignificant effect on user satisfaction